Fabrication of Circular Obelisk-Type Multilayer Microneedles Using Micro-Milling and Spray Deposition - Kim, Min Jung; Park, Seok Chan; Rizal, Binod; Guanes, Giselle; Baek, Seung-Ki; Park, Jung-Hwan; Betz, Amy R.; Choi, Seong-O (Frontiers in Bioengineering and Biotechnology, 2018)
In this study we present the fabrication of multilayer microneedles with circular obelisk and beveled-circular obelisk geometries, which have potential applications in implantable drug delivery devices. Micro-milling was adopted as an environmental-friendly and cost-effective way to fabricate primary metal microneedle masters. Polylactic acid (PLA) microneedles with sharp tips were then obtained by micromolding followed by oxygen plasma etching and used for preparing polydimethylsiloxane (PDMS) microneedle molds. A spray deposition process was employed for microneedle fabrication to facilitate the formation of multilayer microneedles while helping in maintenance of drug stability. Multilayer microneedles were successfully formed by sequential spraying of poly(lactic-co-glycolic acid) (PLGA) and polyvinylpyrrolidone (PVP) solutions into the mold. The fabricated PLGA-PVP multilayer microneedles penetrated the pig cadaver skin without breakage and released dyes in the skin at different rates, which reveals the potential for implantable microneedles enabling controlled release. Mechanical testing demonstrated that the obelisk-shaped microneedles were mechanically stronger than a pyramid-shaped microneedle and suggested that strong adhesion between PLGA and PVP layers was achieved as well. Structural stability and functionality of a model drug, horseradish peroxidase (HRP), upon spray deposition was examined using circular dichroism spectroscopy and enzyme activity assay. HRP retained its secondary structure and activity in PVP, whereas HRP in PLGA showed structural changes and reduced activity. Combination of micro-milling and spray deposition would be an attractive way of fabricating drug-containing polymer microneedles with various geometries while reducing prototyping time and process-induced drug instability.